Effects of buccal misoprostol compared with vaginal misoprostol on first-trimester abortions: a randomized clinical trial - Hosseini, Maryam Sadat; Shirzadi, Nooshin; Amjadi, Nooshin (Researcher Bulletin of Medical Sciences, 2021)
Objective: Misoprostol can be used by different routes in the medical management of abortion. This study aimed to compare the efficacy and safety of buccal and vaginal administration of misoprostol for the completion of first-trimester abortions. Materials and Methods: This study was a randomized clinical trial in which women with first-trimester abortion referred to Imam Hossein Medical Center in 2018 were studied. Women were randomly divided into two groups of buccal or vaginal misoprostol treatment. From the time of drug administration to complete abortion, side effects, duration of drug use until tissue excretion, need for blood transfusion and need for surgical evacuation were recorded and compared in two groups. Results: One-hundred women (each group, 50 patients) were evaluated in this study. There was a significant difference between the two groups regarding the duration of misoprostol use (p-value = 0.028), and it was longer in the buccal group. Besides, there was a significant difference between the two groups in terms of the dose required until the tissue discharge (p-value = 0.034). In the buccal group, patients received higher doses of misoprostol. The rate of fever had a significant difference between the two groups and was more frequent in the vaginal group (p-value=0.023). Conclusion: Vaginal misoprostol can be more effective in treating first-trimester abortions compared to buccal misoprostol and may be associated with longer duration of use and lower required doses.